Mechanistic insights into nutrient profiles, cellulose, and hemicellulose dynamics in red and green Toona sinensis buds during cold storage - Tan, Guo-Fei; Zhao, Qian; Wang, Fu; Li, Shu-Yao; Liu, Zi-Yu; Zhang, Xin-Qi; Zhong, Xiu-Lai; Zhu, Shun-Hua; Lei, Xiu-Juan; Han, Zhong-Min; Zhang, Jian (Frontiers in Plant Science, 2025)
Toona sinensis (T. sinensis) is a popular woody vegetable with distinct red and green varieties in China. Despite its significance, research on the comparative nutrient composition profiles and cellulose and hemicellulose dynamics between these two varieties remains limited. This study comprehensively investigated the refrigerated storage characteristics of T. sinensis buds from multiple aspects, related to cellulose and hemicellulose synthesis. The results showed marked differences between the two varieties during 3 d postharvest storage. Green T. sinensis buds had more severe blackening at the petiole base. Green T. sinensis buds were also richer in vitamin C (Vc), protein, reducing sugars, flavonoids, and total phenols, while red T. sinensis buds had higher total sugar content. In terms of enzyme activities, red T. sinensis buds had elevated β-xylosidase metabolizes hemicellulose content over 28.65 mg·g-1 higher than that of green T. sinensis buds, while green T. sinensis buds increased cellulase (CL) activity led to a hemicellulose content 26.60 mg·g-1 high than red T. sinensis buds. The cell wall thickening and polygonal cell shape during storage were closely associated with the increase in hemicellulose content. Additionally, red T. sinensis buds exhibited elevated CAT and SOD activities in response to oxidative stress induced by increased MDA levels. In summary, green T. sinensis buds demonstrated higher nutritional value but reduced storage stability and enhanced lignification compared to red T. sinensis buds. This research not only provides a multi-dimensional understanding of T. sinensis storage characteristics, but also lays a foundation for the development of scientific storage and preservation methods.